Enantioselective Desymmetrizations Promoted by Bifunctional Organocatalysts - Quintavalla, Arianna; Cerisoli, Lucia; Montroni, Elisa (Current Organocatalysis, 2014)
The enantioselective desymmetrization is regarded as an effective strategy for producing chiral compounds from achiral substrates. The past decade saw the establishment of organocatalysis in organic synthesis and also organocatalytic desymmetrizations have emerged in recent years. In particular, bifunctional organocatalysts have shown the ability to promote enantioselective desymmetrizations enabling simultaneous covalent and/or non-covalent activations of the reagents. Many classes of prochiral and meso compounds were efficiently desymmetrized, being cyclic anhydrides ringopening and diols acylation the most widely employed transformations. The goal of this review is to give a comprehensive overview on the developed strategies in the field of the enantioselective desymmetrizations promoted by bifunctional organocatalysts.
Keywords: desymmetrization